2018
DOI: 10.1007/s40333-018-0012-3
|View full text |Cite
|
Sign up to set email alerts
|

Simulating long-term effect of Hyrcanian forest loss on phosphorus loading at the sub-watershed level

Abstract: Conversion of forest land to farmland in the Hyrcanian forest of northern Iran increases the nutrient input, especially the phosphorus (P) nutrient, thus impacting the water quality. Modeling the effect of forest loss on surface water quality provides valuable information for forest management. This study predicts the future impacts of forest loss between 2010 and 2040 on P loading in the Tajan River watershed at the sub-watershed level. To understand drivers of the land cover, we used Land Change Modeler (LCM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…An emerging example of such valuable forest species is Hyrcanian that has a long history (arised in the Jurassic Period) and is among the world's most valuable natural resources; the rapid decline in its area has been a major concern in the recent years. Rajaei et al [4] studied the LULC dynamics in the northern parts of Iran and revealed that, in the past four decades, the forest area decreased by 3.0%, while dry farming increased by 9.2%. Emadodin [5] reported that the LULC change in Iran has increased over the past 50 years and is expected to accelerate in the future.…”
Section: Introductionmentioning
confidence: 99%
“…An emerging example of such valuable forest species is Hyrcanian that has a long history (arised in the Jurassic Period) and is among the world's most valuable natural resources; the rapid decline in its area has been a major concern in the recent years. Rajaei et al [4] studied the LULC dynamics in the northern parts of Iran and revealed that, in the past four decades, the forest area decreased by 3.0%, while dry farming increased by 9.2%. Emadodin [5] reported that the LULC change in Iran has increased over the past 50 years and is expected to accelerate in the future.…”
Section: Introductionmentioning
confidence: 99%